Ribbon interconnection of 6" BC-BJ solar cells. (September 2017) - Walter, Johann; Rendler, Li C.; Halm, Andreas; Mihailetchi, Valentin; Kraft, Achim; Eitner, Ulrich
Abstract: This work presents an interconnection approach for 6" back-contact back-junction (BC-BJ) solar cells by using conventional solder-coated copper ribbons with implemented wave structures for thermomechanical stress relief. We developed a process for production and advanced mechanical and electrical characterization for these interconnectors. In our study, mechanical stress is reduced up to 96.6 % (for ribbons) and up to 81 % (for wires) compared to non-structured interconnectors. In electrical terms, the relative effective resistance of the interconnector is increased by 3.1 % (for ribbons) and by 6.4 % (for wires). In general both, ribbons and wires, are suitable for the interconnection of 6" BC-BJ solar cells. A 4-cell module with 19.94 % efficiency in a standard module setup with 21.09 % - 21.18 % 6" BC-BJ ZEBRA cells (CTMpower = -3.8 %) is manufactured. For interconnection 8 modified ribbons (1.5 x 0.2 mm²) are used on the rear side. The cells feature a multilayer metallization with a low temperature paste. The module passes TC-200 according to IEC 61215 without degradation. Our cost analysis shows that such a stress relief structure can be realized with additional material costs of lower than 0.2 € for a 60 cell full size module.